Cultural Ambivalence in Murakami’s Norwegian Wood - Adhikari, Rishiram (NUTA Journal, 2023)
This study analyzes Haruki Murakami's novel Norwegian Wood from the perspective of cultural ambivalence. Toru, the main character of the novel neither totally follows western culture nor rejects it. He adopts western culture in the name of becomes modernize and also continue the Japanese culture for the sake of preserving cultural identities. In the same manner Naoko, Reliko and Midori Kobayashi also face the problem in their life and are being victimized the situation of cultural ambivalence. The main concern of the study is to analyze the situation of Japanese youth during the time of World War II. The study followed qualitative research design and analyzed analyzes novel based on textual analysis. Closed reading of the text is the main tools of data collection and only the secondary sources of data were used in this study gathered from library research. Books, articles, journals and Google based information were the main source of secondary data. Conclusion has been made on the basis of interpretation and analysis of the collected data. From the interpretation of the text, it is found that characters of the novel have been facing the problem of identity crisis in their life due to cultural hegemony of America after the World War II. In the World War II Japan had defeated from the American troop and feel humiliation in the defeated situation that also affected in culture.